The Role of Family Involvement in Moderating The Relationship Between Company Characteristics and Dividend Policy in Indonesia - Madyan, Muhammad; Sasikirono, Nugroho; Kusmayana, Wida; Meidiaswati, Harlina (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
This study seeks out the relationship between the characteristics of companies and dividend policy, as well as the role of family involvement as a moderator of such relationships. This study utilized a purposive sampling method. We conducted the analysis by multiple linear regression and moderated regression analysis. The number of samples in this study is 192 observations in non-financial companies listed on the LQ45 index. The Result shows that profitability, size, and investment opportunities have a positive effect on dividend payout ratio. Meanwhile, financial leverage has a negative relationship with the dividend payout ratio. Family involvement weakens the positive influence of profitability on dividend policy but strengthens the positive effect of investment opportunities. Family involvement does not moderate the effect of size, and financial leverage on dividend policy.